Labour Market Inequalities in India: Dimensions and Policies. Issue 2 (August 2018) - Dev, S. Mahendra
This article deals with dimensions of labour market inequalities and policies for reducing these inequalities. The problem of inequality can be found across sectors, wages and earnings, quality of work, labour market access and, between organized and unorganized sector. Labour market segmentation is another important issue regarding inequalities. Reducing labour market inequalities is important for the sustainability of growth, reduction in poverty and a rise in human development in India. Macro policies, sectoral policies, skill related policies, education and social protection policies are important for reduction of labour market inequalities. At the global level, technological change has been one of the factors responsible for increasing labour market inequalities between skilled and unskilled workers. India has to be prepared for technological revolution and its implication for employment. The country has to address the "fundamental challenge" of improving human capital for all the workers in order to reduce inequalities. Political economy issues have to be tackled in order to address raising inequalities.